QUESTIONS OF HUMANIST ANTHROPOCENTRISM IN THE PHILOSOPHY OF MICHEL MONTAIN (Scientific journal of the Fergana State University, 2023)
The article reveals the issues of humanistic anthropocentrism of the European Renaissance on the example of the socio-philosophical teaching of Michel Montaigne. Also important for young people are the humanistic essence of the ideas of self-consciousness, faith, purity of conscience in the work of the thinker "Experiments", in-depth study and evaluation of the eternal heritage, the acquisition of modern scientific achievements, responsibility and noble qualities. describes the formation of a spiritual image.